2018
DOI: 10.3390/polym10040404
|View full text |Cite
|
Sign up to set email alerts
|

Facile and Eco-Friendly Fabrication of Colored and Bioactive Silk Materials Using Silver Nanoparticles Synthesized by Two Flavonoids

Abstract: Recently, there has been an increasing tendency towards the functionalization of silk using silver nanoparticles (AgNPs) to inhibit bacterial multiplication and disease spread. Considering environmental factors and sustainable development, the preparation of AgNPs using natural extracts is becoming a research hotspot. This study aims at fabricating colored and bioactive silk fabric using AgNPs synthesized by two representative flavonoids (quercetin and rutin). The effects of pH, temperature, and flavonoid conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 50 publications
2
14
0
Order By: Relevance
“…It was determined in more advanced research that quince leaf extracts are essentially made up of polyphenols that are enriched by functional groups like OH [52,53]. Therefore, on the basis of earlier studies [44,45,48,54] and FTIR analysis of the current study, Figure 3 presents the suggested scheme for silver ion reduction using the flavonoids of quercetin of quince leaf extract solution. Using density functional theory (DFT) analysis, it was shown in an earlier study that there are lower O–H bond dissociation energies of –OH groups of the catechol moiety of flavonoids of quercetin of quince leaf extract solution compared to other –OH groups existing in flavonoids [48].…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…It was determined in more advanced research that quince leaf extracts are essentially made up of polyphenols that are enriched by functional groups like OH [52,53]. Therefore, on the basis of earlier studies [44,45,48,54] and FTIR analysis of the current study, Figure 3 presents the suggested scheme for silver ion reduction using the flavonoids of quercetin of quince leaf extract solution. Using density functional theory (DFT) analysis, it was shown in an earlier study that there are lower O–H bond dissociation energies of –OH groups of the catechol moiety of flavonoids of quercetin of quince leaf extract solution compared to other –OH groups existing in flavonoids [48].…”
Section: Resultsmentioning
confidence: 93%
“…Hence, Ag +1 cation reduction is coupled with the oxidation of hydroxyl group of polyphenols [55]. Commonly, the Ag NPs formation mechanism in the existence of flavonoids lies at the group of diorthohydroxyl in their B-ring that enhances the Ag +1 cation reduction to Ag NPs via the release of two electrons [54].…”
Section: Resultsmentioning
confidence: 99%
“…In situ NP synthesis in silk materials has also been developed using caffeic acid, flavonoids, vitamin C, citrate, Rhizophora apiculata leaf extracts, Streptomyces cell extracts or honeysuckle extracts as reducing agents (Dhas et al, 2015 ; Meng et al, 2016 ; Shahid et al, 2017 ; Zhou and Tang, 2018a , b ; Baygar et al, 2019 ; Gao et al, 2019 ). The materials acquired antibacterial activities and showed no cytotoxic effects.…”
Section: Silk-based Bionanocompositesmentioning
confidence: 99%
“…The microbial growth and multiplication cause the generation of fetid odors and mildew, the deterioration and discoloration of silk fiber, skin infection, and allergic responses [2]. A series of synthetic and natural antibacterial agents have been applied in the antibacterial treatment of silk, including quaternary ammonium compounds [13], inorganic nano-materials [14], chitosan [15,16], and natural bioactive compounds [3,17]. On the other hand, the active ingredients of natural plant extracts (e.g., curcumin, baicalin, quercetin, rutin, and chlorogenic acid) have been used to upgrade the antioxidant property of silk [3,8,18,19].…”
Section: Introductionmentioning
confidence: 99%